Handbook of research on engineering innovations and technology management in organizations - Gaur, Loveleen; Solanki, Arun 1985-; Jain, Vishal 1983-; Khazanchi, Deepak (IGI Global, 2020)
"This book explores emerging trends in engineering innovations and technology management within organizations"--